Can we "Claim" the Workforce? A Labor-Focused Agenda for Economic Development in the Face of an Uncertain Future. Issue 1 (February 2023) - Chapple, Karen; Schmahmann, Laura
The COVID-19 pandemic accelerated three trends that were already transforming economic development theory and practice. A backlash to economic restructuring and inequality, driven by globalization and technology, is now manifesting in reshoring and union movements. The resurgence of small and midsized cities, originally driven by increasing housing costs in coastal cities, has been reinforced by a rise in remote work. The uncertainty of today's complex economy is exacerbating long-term challenges of tracking economic change, making "shoot anything that flies" more important than ever. These trends highlight the need to focus economic development on building and supporting the workforce.